Racism in Roald Dahl’s The BFG: A Social Criticism or White Supremacy Tendency? - Jeanyfer Tanusy (k@ta: A Biannual Publication on the Study of Languange and Literature, 2020)
Children stories can be a powerful tool for a writer to present their views of the world around them, both positive or negative ones. This article attempts to examine the message beneath a children novel, The BFG by Roald Dahl by employing Barthes’ five systems of codes. Focusing on the writerly codes, this descriptive qualitative research emphasizes on analyzing the smallest units of the stories, or the lexias. Each lexia is categorized into the three writerly codes to reveal the underlying message in the story. The findings show that despite The BFG being a children book, it consists of some serious social issues like racism. Another thing found in the research is that the issue can lead to a double meaning—whether Dahl intends to raise social awareness or that he wants to subtly say that he himself thinks of other races as inferior.